Choice as a Meaning-Making Device for Maximizers: Evidence From Reactance to Restrictions of Choice Freedom During Lockdown - Kokkoris, Michail D. (Frontiers in Psychology, 2020)
The current research investigates maximizers’ responses to restrictions of choice freedom during lockdown in the context of the COVID-19 pandemic. Having as a starting point the assumption that for maximizers choice is constitutive of identity, this research proposes that maximizing is associated with search for existential meaning in life. In turn, maximizers’ propensity to search for meaning is associated with a higher susceptibility to experience reactance when their freedom of choice is restricted, which is further associated with higher engagement in online shopping during lockdown presumably as a means to combat reactance and restore choice freedom. Using the lockdown in spring 2020 as a naturalistic context to study consumer responses to restrictions of choice freedom, results of an online study in Austria support these predictions. These findings advance a view of maximizers as ‘lay existentialists’, who view choice as a meaning-making device that is tightly linked to their sense of identity. As a result, when their choice freedom is threatened, maximizers may respond with higher reactance and engage in restorative actions.